سندھ ٹی براہوئی ادب نا تاریخ: History of Brahui literature in Sindh - Bangulzai, Abdul Qayyum Johar; Sadiq, Abdul Haleem (Al-Burz, 2016)
The purpose of this research article is to investigate the literary development of Brahui Language in Sindh because a great Number of Brahui People resides in the different parts of Sindh. They had produced poetry and prose in their language. They are still creating Brahui Literature. Their contribution in the development of Brahui literature is enormous in this respect. In addition, Non Brahui Sindhi poets and prose writers also came under the influence of Brahui literature. Therefore, they also contributed to it. For example: Shah Abdul Latif Bhitai, Sachal Sarmast, and others were influenced by Brahui and used Brahui words and lines in their Sindhi poetry. Maulana Muhammad Omer Dinpoori’s Madersa-Islamia Brahuia Dinpoori Shikarpur Sindh enriched Brahui Literature with Islamic Thoughts, rules and Traditions. The researcher attempts to trace historical development of Brahui literature in this ongoing research study.